GAMBARAN KUALITAS TIDUR BAYI USIA 6-12 BULAN - mellysa rosalina (Jurnal Medika Hutama, 2022)
Introduction: Sleep is one of the basic human needs. During sleep there is a process of repairing the body’s organs. The quality of baby sleep is seen from the baby’s ability to sleep and get the amount of rest according to his needs. This study aims to determine the quality of sleep for infants aged 6-12 months. Method: This reseach design is a simple descriptive to describe a phenomenon. This reseach was conducted in the working area of Rejosari Health Center with a total sample of 148 respondents who were taken by accidental sampling technique. The measuring instrument used was a questionnaire about the quality of sleep in infants adopted from the A Brief Infant Sleep Quesionaire (BISQ) with 6 questions consisting of: sleep duration at night, duration of sleep at night, frequency of waking at night, duration of waking up at night, when it starts sleeping again, and the baby is fussy and crying. The analysis used was univariate analysis to describe the characteristics and quality of baby sleep. Result: Most of the characteristics of respondents were at the age of 12 months (31,1%). Most of the sex was male (57,4%). Most religious characteristics are Islam (92,6%). The results showed that the average total sleep quality of infants was not good (73%). Conclussion: The results of this study suggest that the health center where the study is to pay more attention to the problem of sleep quality in infants.